Post-covid syndrome – current challenge in the work of the general practitioner - Pušica, Irena; Lončar, Ana (General Practice, 2024)
Introduction. Post-COVID syndrome is characterized by a wide range of clinical symptoms that persist for more than three months after the initial SARS-CoV-2 infection. Objective. Our objective was to confirm and explore the long-term effects of post-COVID syndrome, the prevalence of individual symptoms, and the factors that may influence their occurrence. Method. In our study, we conducted a cross-sectional analysis on patients who had previously been infected with SARS-CoV-2. Participants were requested to complete the questionnaire during the latter part of 2023. The data was examined using descriptive statistics, the Kruskal-Wallis test, and the Bonferroni test for multiple pair comparisons using SPSS 26. A p-value <0.05 was considered statistically significant. Results. Out of a total of 90 participants, 15.6% did not experience post-COVID symptoms. However, 24.4% experienced symptoms that persisted for longer than six months. The most common symptoms reported were rapid fatigue (60%), chronic fatigue (53.3%), and difficulty concentrating (45.6%). There was a significant difference in the occurrence of tachycardia, sweating, and constipation among different age groups (p<0.05). Additionally, the presence of cough, chest pain, constipation, and sexual disorders showed significant differences in relation to body mass index, (p<0.05). Furthermore, significant differences in the occurrence of nightmares, headaches, anxiety, abdominal pain, and diarrhea were noticed in relation to cigarette smoking status (p<0.05). Lastly, in relation to comorbidities, there was a statistically significant difference in the occurrence of hair loss (p<0.05). Conclusion. A holistic approach is necessary in treating a patient with post-COVID. Therefore, the role of the general practitioner (GP) is crucial. Keywords: SARS-CoV-